Pengembangan Alat Peraga Pembelajaran Berbasis Etnomatematika Pada Rumah Gadang di Kelas IX SMPN 3 Mapat Tunggul Kabupaten Pasaman Tahun Pelajaran 2022/2023 - Nurvadilla, Nurvadilla; Isnaniah, Isnaniah; Risnawita, Risnawita; Rahmatq, Tasnim (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This research was motivated by the problems found in grade IX SMPN 03 Mapat Tunggul, namely the lack of learning media, the teaching aids used were not cultural-based, the teaching aids in schools were teaching aids that were not in accordance with the characteristics of students, resulting in students finding it difficult to understand the mathematical concepts learned. This research is a development research or Research and Development ( R & D ) with the development model Hannafin & Peck. Based on the development research that has been done, props were obtained with a very valid criterion of 82.33%, for the level of practicality is on a very practical criterion of 88.25%, for the level of effectiveness is on a very effective criterion of 80.95%. So it can be concluded that the Ethnomathematics-Based Mathematics Learning Aids at Rumah Gadang in grade IX SMPN 03 Mapat Tunggul Pasaman Regency for the 2022/2023 academic year that were developed are valid, practical, and effective.